Decision-Making System for Selecting Alternative Product Purchase Stores in Tokopedia Using A Combination of SAW and TOPSIS - Yanuar Nurdiansyah; M Zukhrofi Ardi; M Arief Hidayat (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
In the era of advancing digital technology enabling online business transactions, e-commerce platforms like Tokopedia have rapidly grown in Indonesia, providing consumers with a wide array of products and services. However, this abundance of choices often leads to consumer confusion when selecting alternative stores for their purchases. Additionally, Tokopedia's search filter feature is limited, merely sorting products based on selected criteria without considering the consumer's specific needs. To address these issues, a decision-making system is essential, aiding consumers in choosing products from alternative stores that best align with their individual preferences and predetermined criteria. This study proposes a combined methodology employing the Simple Additive Weighting (SAW) method and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). Initially, the SAW method normalizes values (r), which are subsequently ranked using the TOPSIS method to generate recommendations for alternative stores based on input criteria and weights. The adoption of this decision-making system is poised to enhance the online shopping experience for Tokopedia users by providing well-informed recommendations, improving overall satisfaction, and streamlining the purchasing process. In conclusion, this research offers a promising approach to addressing the challenges posed by the abundance of choices in online retail, ultimately benefiting both consumers and online businesses.